GE_GERICHTE C/28798/2010 vom 20. Dezember 2013 - GE Cour de justice (2013)
SIGNALISATION ROUTIÈRE; DÉPASSEMENT(CIRCULATION); DOMMAGE MÉNAGER | LCR.35.1; LCR.36.3; LCR.47.2; LCR.61.1; OSR.74.4; CO.46.1